Pengaruh Kompetensi Dan Independensi Terhadap Kualitas Audit Di Inspektorat Kota Padang Dengan Kompetensi Bukti Audit Sebagai Variabel Intervening - Rahmaita .; Nikita Ananda (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of auditor competence and independence on audit quality, with audit evidence competence as an intervening variable at the Inspectorate of Padang City. Using a quantitative survey approach, the study involved the entire population of the Government Internal Supervisory Apparatus (APIP), totaling 64 respondents, through a census method. Data were analyzed using Structural Equation Modeling (SEM-PLS). The results indicate that both competence and independence have a positive and significant impact on audit quality and audit evidence competence. Furthermore, audit evidence competence significantly affects audit quality and serves as a partial mediator for the influence of competence and independence on audit quality. These findings emphasize that improving audit quality requires the integration of technical expertise, mental integrity, and sharpness in evaluating relevant and reliable audit evidence. Strengthening these aspects is crucial to supporting the effectiveness of local government internal supervision.